2004
DOI: 10.1370/afm.122
|View full text |Cite
|
Sign up to set email alerts
|

Brief Physician Advice For High-Risk Drinking Among Young Adults

Abstract: BACKGROUND High-risk alcohol use in persons 18 to 30 years of age is a critical public health problem. It is the number 1 cause of death in this population. This article reports the results of a subanalysis of young adults (aged 18 to 30 years) who participated in Project TrEAT (Trial of Early Alcohol Treatment) conducted in the offi ces of 64 primary care physicians located in 10 counties in southern Wisconsin.METHODS Project TrEAT was a randomized clinical trial designed to test the efficacy of a brief inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 23 publications
1
58
1
Order By: Relevance
“…Evidence favours brief interventions by GPs to prevent harm associated with tobacco or alcohol use. [18][19][20][21][22][23] Similar interventions have potential in addressing excessive cannabis use. 24 Adolescent health care is typically ambulatory care; 70-90% of young people are in contact with GPs at least once a year.…”
Section: The Role Of Gps In Addressing Excessive Cannabis Use In Younmentioning
confidence: 99%
“…Evidence favours brief interventions by GPs to prevent harm associated with tobacco or alcohol use. [18][19][20][21][22][23] Similar interventions have potential in addressing excessive cannabis use. 24 Adolescent health care is typically ambulatory care; 70-90% of young people are in contact with GPs at least once a year.…”
Section: The Role Of Gps In Addressing Excessive Cannabis Use In Younmentioning
confidence: 99%
“…15 To meet the needs of both providers and patients, we developed a computerfacilitated screening and brief advice (cSBA) system consisting of a computerized screening and educational component before the visit, and provider advice during the visit. There is substantial evidence from studies conducted in the United States, [16][17][18][19][20][21][22] and other countries 17,20,23,24 supporting the effectiveness of screening and brief physician advice among adult primary care patients, especially in the reduction of harmful drinking and its associated consequences (eg, motor vehicle crashes, emergency department visits). [16][17][18][19] It is unknown, however, whether these findings are generalizable to younger patients, as there have been fewer studies among adolescents in primary care.…”
mentioning
confidence: 99%
“…There is substantial evidence from studies conducted in the United States, [16][17][18][19][20][21][22] and other countries 17,20,23,24 supporting the effectiveness of screening and brief physician advice among adult primary care patients, especially in the reduction of harmful drinking and its associated consequences (eg, motor vehicle crashes, emergency department visits). [16][17][18][19] It is unknown, however, whether these findings are generalizable to younger patients, as there have been fewer studies among adolescents in primary care. 25,26 Existing studies suggest that primary care screening and brief interventions can positively impact adolescent health issues, such as tobacco use, [27][28][29][30] nutrition and physical activity, 31,32 and depression.…”
mentioning
confidence: 99%
“…Multicontact BMIs delivered by primary health care providers have been shown to reduce alcohol consumption by three to nine drinks per week in adult patients (Whitlock et al, 2004). Within the timeframe of a standard primary care visit, multiple studies demonstrated that BMIs consistently produced reductions in alcohol consumption (Bertholet et al, 2005;Fleming et al, 1997;Grossberg et al, 2004;Kaner et al, 2007). Screening and brief counseling for alcohol misuse in primary care also are cost effective (Solberg et al, 2008).…”
mentioning
confidence: 99%